Laboratory indices and survival of urinary bladder cancer patients - L. A. Derzhavets (Сибирский онкологический журнал, 2016)
Current laboratory techniques were used for evaluation of tumor markers, growth factors, angiogenesis, intercellular adhesion in biological fluids of 349 patients with nonmusculo-invasive urinary bladder cancer (264 patients had a single tumor and 285 presented with multiple tumor foci). An analysis was made of the correlation between four indices most closely related with the number of tumor foci in the bladder, and patient survival. The log-rank test found a correlation between the levels of UBC, sICAM, TPS, p185 in biological fluids, and survival (Plog-rank<0,05). The values of UBC in urine and sICAM in blood serum affect overall, cancer-specific, recurrence-free survivals of patients with either a single tumor focus or multiple tumor foci in the bladder. TPS blood levels affect the same survivals but only in patients with a single tumor focus. As regards p185, the level of this protein has a significant impact on all the calculated survivals of patients with nonmusculo-invasive bladder cancer. Multivariate analysis including all the four indices, with Cox proportional hazards regression model, found that a high blood level of p185 is an unfavourable prognostic factor for recurrence-free survival: with p185 concentration <4,43 ng/ml, 5-year recurrence-free survival of patients with a single tumor focus in the bladder was 95,9 % and with p185≥4,43 ng/ml it was 64,1 %; in patients with multiple tumor foci it was 83,6 % with p185<5,7 ng/ml and 30,0 % with p185≥5,7 ng/ml.